Degradation of fabrics used in military fragment protective clothing due to selected laundering regimes - Helliker, Mark (Cranfield University, 2018)
With the introduction of fragment protective fabrics into combat clothing, there was a need to understand the effect of laundering on the performance of these fabrics. This thesis investigated the effect of typical laundering regimes on selected ballistic protective fabrics representative of those suitable for clothing applications. This study presents evidence that knitted silk and felted ultra-high molecular weight polyethylene retained their ballistic protective performance after laundering. The para-aramid fabrics showed significant improvement from laundering. The dimensional stability of the selected fabrics was affected by laundering and the effect was cumulative. The damage imparted to the fibres was determined to be due to mechanical wear. This mechanical wear was significantly increased when the fabrics were wet. This was due to the water increasing the friction between fibres during the laundering process. The fabrics investigated were shown to be suitable for use in fragment protective clothing, and were more robust than was generally considered.
Keywords: Ballistic testing; Para-aramid fabric; Silk; Dimensional stability; Water